The EU Indo-Pacific Bid Sailing Through Economic and Security Competition - Fasulo, Filippo (ISPI Publications, 2023)
Over the past five years, the Indo-Pacific region's importance for Europe has grown significantly. However, the launch of the EU Strategy for cooperation in the Indo-Pacific in September 2021 and its subsequent implementation have been affected by growing polarisation between the US and China, and by a fast-changing scenario caused by the Russian invasion of Ukraine. This Report examines the state and perspectives of the EU's Indo-Pacific strategy, 18 months after its launch. Are there avenues for cooperation with regional military initiatives, such as the QUAD? How is the economic landscape changing, in particular after the start of negotiations for the Indo-Pacific Economic Framework for Prosperity (IPEF)? What are the main strategies of Indo-Pacific countries for the green transition? And how do the US, China, and ASEAN countries view and act in the Indo-Pacific region?